4t+(3+5t)(4t)=x

Simple and best practice solution for 4t+(3+5t)(4t)=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4t+(3+5t)(4t)=x equation:


Simplifying
4t + (3 + 5t)(4t) = x

Remove parenthesis around (4t)
4t + (3 + 5t) * 4t = x

Reorder the terms for easier multiplication:
4t + 4t(3 + 5t) = x
4t + (3 * 4t + 5t * 4t) = x
4t + (12t + 20t2) = x

Combine like terms: 4t + 12t = 16t
16t + 20t2 = x

Solving
16t + 20t2 = x

Solving for variable 't'.

Combine like terms: x + -1x = 0
16t + 20t2 + -1x = 0

The solution to this equation could not be determined.

See similar equations:

| 209=16x^2-32x-15 | | 10x+3=9x+9 | | -7+r=-15 | | 16m-9=-8 | | -16(5)2+200(5)+6=-400+1000+6 | | -15-7x=6-3x | | 4(11x-14)=2(1-7x) | | 11a^2-32a-3=0 | | (x+3)(x+13)=0 | | -2(x-4)-x=-(4x-10) | | 2x-7=22 | | 9+4n=15 | | y=x^2-8x+15 | | 8g-12-2g=36 | | 12(b+12)+6=9(b-2)+9b | | 13x+-7(-3x-1)=-63 | | 5x=2+8x | | r^2+12r-64=-52 | | 2x-(x-24)=90 | | -4(m+10)=8m+4(-12-2m) | | 2y^2+4=12 | | 10-12(1-x)=8(-12+6x)-14 | | (x+13)(x+13)=25 | | 3p+8p=4(p+6) | | 85+5(l-11)=120 | | 2+8x=5-7x | | 13-4(p-2)=1 | | 4x-3=5x+9 | | 4y^4-37y^2=-9 | | -6x+3=-45 | | (7x-5)(7x-5)-10=0 | | 2.5k+2=7 |

Equations solver categories